PERLINDUNGAN HUKUM TERHADAP INVESTOR ASING ATAS PENCABUTAN IJIN USAHA - Ni Putu Alya Regina Putri; I Nyoman Putu Budiartha; Anak Agung Istri Agung (CV. Lafadz Jaya, 2026)
Foreign investment is a crucial element in Indonesia's economic development. However, law enforcement against foreign investors still faces various challenges, particularly related to the revocation of business licenses, which can potentially lead to disputes. In late 2024, the Indonesian government, through the Investment Coordinating Board (BKPM), revoked the Business Identification Numbers (NIB) of 267 foreign investment (PMA) companies in Bali for failing to meet minimum capital requirements. This study aims to examine the process of revoking business licenses for foreign investors and the legal protection provided by the government following such revocation. The study employed a normative juridical method with a statutory and conceptual approach. The results indicate that business license revocation is carried out through a risk-based OSS mechanism and investment realization audits. Legal protection is provided in the form of preventive protection (procedural certainty, regulatory transparency, the OSS-RBA system) and repressive protection (complaint mechanisms, administrative dispute resolution, and international investment arbitration). This study emphasizes the importance of balancing state authority in regulating investment with investors' rights to legal certainty.